(untitled) (Research, Society and Development, 2020)
Classified as a category of Brazilian Conservation Unit for sustainable use, the Sustainable Development Reserve of Barra do Una (SDRBU) presents notorious biodiversity of medicinal plants traditionally used throughout the generations to treat different diseases. Thus, ethnopharmacological data gathered by the present study are essential to document and preserve knowledge of the local population of this area. The study aimed to obtain ethnopharmacological information about the medicinal plants used by the local population of the SDRBU. Ethnopharmacological data were collected through semi-structured interviews with 37 informants from the population of the SDRBU. The plant species mentioned were collected through the guided tour technique and taxonomic identification was performed. Informant’s Consensus Factor and Fidelity Level were used to determine the importance of medicinal plant resources. Pharmacological validation and a systematic review of phytochemical compounds for the mentioned species was also performed. For species without information on phytochemical constituents it was carried out a phytochemical screening. 103 plants were cited, of which 70 could be identified at species level. Among plants that were identified at species level, only 21 have pharmacological validation in pharmacopoeias and monographs. Tabebuia cassinoides (Lam.) DC. and Imperata tenuis Hack. presented no information in literature on phytochemical constituent and biological activities and thus were analyzed through phytochemical screening. The present study documented for the first time the ethnopharmacology of medicinal plants of the community of the SDRBU.